Tinjauan Yuridis Terhadap Petitum Cerai Talak dan Cerai Gugat di Pengadilan Agama - Siti Rohmatul Ilahiya; Ahmad Musadad (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The purpose of this study is to provide broader knowledge to the people of Bangkalan regarding the rights that must be defended in the petitum divorce and mutual divorce in the Bangkalan Religious Court. The research method used in this study is normative juridical, using approaches (law approach), (comparative approach), and (conceptual approach). The results of this study show that the highest decision in the household rests with the husband, but when carrying out a divorce, the highest decision rests with the judge's decision. The parties can defend their rights through a petitum for divorce, including imposing divorce on the husband, and the wife retaining a living, mut’ah (gift), living during the idah period, joint assets and others in accordance with Law no. 1 of 1974 concerning Marriage and Compilation of Islamic LawLaw.